2018
DOI: 10.1093/cvr/cvy015
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma catecholamines functionally compensate for the reduced myogenic tone in smooth muscle STIM1 knockout mice but with deleterious cardiac effects

Abstract: STIM1 deletion in smooth muscle results in attenuated myogenic tone and cytoskeletal defects with detrimental effects on the mechanical properties of arterial tissue. Although BP is maintained by elevated circulating catecholamine, this compensatory stimulation has a deleterious long-term effect on the myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
(67 reference statements)
1
5
2
Order By: Relevance
“…Diminished arterial contractility following Stim1 knockout resulted in a drop in arterial BP, probably due to decreased total peripheral resistance. This finding differs from previous reports by other groups showing that, although myogenic tone and phenylephrine-induced vasoconstriction was blunted in mesenteric arteries from a constitutive SMC-specific STIM1-knockout model, resting BP was not affected in this model (81)(82)(83). This difference is likely due to elevated levels of circulating catecholamines, which increase HR and cardiac output and thereby compensate for diminished vascular resistance (83).…”
Section: Discussioncontrasting
confidence: 92%
“…Diminished arterial contractility following Stim1 knockout resulted in a drop in arterial BP, probably due to decreased total peripheral resistance. This finding differs from previous reports by other groups showing that, although myogenic tone and phenylephrine-induced vasoconstriction was blunted in mesenteric arteries from a constitutive SMC-specific STIM1-knockout model, resting BP was not affected in this model (81)(82)(83). This difference is likely due to elevated levels of circulating catecholamines, which increase HR and cardiac output and thereby compensate for diminished vascular resistance (83).…”
Section: Discussioncontrasting
confidence: 92%
“…This finding differs from previous reports by other groups showing that, although myogenic tone and phenylephrine-induced vasoconstriction was blunted in mesenteric arteries from a constitutive SMC-specific STIM1-knockout model, resting BP was not affected in this model(75)(76)(77). This difference is likely due to elevated levels of circulating catecholamines, which increase HR and cardiac output and thereby compensate for diminished vascular resistance(77).In summary, our data demonstrate a vital role for STIM1 in the formation and maintenance of critical Ca 2+ -signaling microdomains in contractile VSMCs that is independent of SR Ca 2+ store depletion. Disruptions in cellular architecture at the nanoscale level associated with the loss of STIM1 resulted in arterial dysfunction and impaired BP regulation, highlighting the essential nature of SR-PM junctions in cardiovascular control.…”
contrasting
confidence: 99%
“…In each cell, APs were first recorded in a control extracellular solution containing 1 nM of the βAR agonist isoproterenol (Iso) and then upon wash-on of 1 µM Iso. 1 nM Iso was used in the control solution as in previous studies (Larson et al, 2013; Peters et al, 2021) because it mimics the resting catecholamine levels in mice (Pichavaram et al, 2018; Lucot et al, 2005) and humans (Messan et al, 2017). We confirmed that 1 nM Iso did not increase AP firing rate compared to a solution lacking Iso (304 ± 15 bpm in 1 nM, N = 50 vs. 313 ± 31 bpm in 0 nM, N = 19; P = 0.9879).…”
Section: Resultsmentioning
confidence: 99%